Treatment of refractory ulcerative necrobiosis lipoidica diabeticorum with oral thalidomide - Swapnil D Shah; Girish V Kale (Wolters Kluwer Medknow Publications, 2016)
Ulcerative necrobiosis lipoidica (NL) in diabetic patients is a rare, painful condition. It is a difficult-to-treat condition, impairing quality of life of patients. Although various drugs have been tried, none of them is consistently effective. Biologics in the form of TNF-alpha inhibitors show promising results in the treatment. But because of their high cost we chose thalidomide, which also has TNF-alpha inhibiting properties to successfully treat a long-standing case of ulcerative NL, which was refractory to various treatment modalities.